Accumulation of iron oxide nanoparticles by cultured primary neurons. (February 2015) - Petters, Charlotte; Dringen, Ralf
Graphical Abstract: Highlights: Iron oxide nanoparticles are not acutely toxic for cultured neurons. Neurons efficiently accumulate iron oxide nanoparticles. The presence of serum lowers the accumulation of iron oxide nanoparticles. Clathrin-mediated endocytosis is involved in neuronal nanoparticle uptake. Abstract: Magnetic iron oxide nanoparticles (IONPs) are frequently used for biomedical applications. Although nanoparticles can enter the brain, little is known so far on the uptake of IONPs in neurons and on their neurotoxic potential. Hence, we applied dimercaptosuccinate (DMSA)-coated IONPs to cultured primary rat cerebellar granule neurons. These IONPs had average hydrodynamic diameters of around 80 nm and 120 nm when dispersed in incubation medium in the absence and the presence of 10% fetal calf serum, respectively. Acute exposure of neurons with IONPs for up to 6 h did neither alter the cell morphology nor compromise cell viability, although neurons accumulated large amounts of IONPs in a time- and concentration-dependent manner which caused delayed toxicity. For the first 30 min of incubation of neurons at 37 °C with IONPs the cellular iron content increased proportionally to the concentration of IONPs applied irrespective of the absence and the presence of serum. IONP-exposure in the absence of serum generated maximal cellular iron contents of around 3000 nmol iron/mg protein after 4 h of incubation, while the accumulation in the presence of 10% serum was slower and reached already within 1 h maximal values of around 450 nmol iron/mg protein. For both incubation conditions was the increase in cellular iron contents significantly lowered by reducing the incubation temperature to 4 °C. Application of inhibitors of endocytotic pathways did not affect neuronal IONP accumulation in the absence of serum, while inhibitors of clathrin-mediated endocytosis lowered significantly the IONP accumulation in the presence of serum. These data demonstrate that DMSA-coated IONPs are not acutely toxic to cultured neurons and that a protein corona around the particles strongly affects their interaction with neurons.